E-MONEY DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Muhammad Ridwan Firdaus (TAHKIM, 2018)
Money as a medium of exchange in economic activities always changes, both in form, intrinsic value, and extrinsic value. Islam as a universal religion and as a way of life, regulates new symptoms that arise in society. The halal use of electronic money is still in doubt by the public. Because the form that is not visible is only how many numbers, and in the form of digital code on a chip or server. This goal aims to find the common value and position of electronic money. Research is limited to tcash issued by PT. Telkomsel. The results of the study found that electronic money is only a service offered by publishers to simplify and streamline the process of economic transactions.